Analysis of the readiness for the treatment in alcoholics in a treatment center (Archives of Clinical Psychiatry, 2005)
The aim of this research was to verify the readiness for the treatment in alcoholics who were taking part of a therapeutical intervention, following the Minnesota Model. A sample of 25 moderate and severe level alcoholists took part on this research. They ranged from 23 to 60 years of age, both male and female. The scale SADD and SOCRATES were applied during the first interview, in the beginning of the treatment. Three additional interviews were performed in the middle, at the end and one month after the treatment, to appraise the readiness for the treatment through SOCRATES scale. The results showed that, although there had been 64% of adhesion to treatment, there was not reduction of ambivalence of the alcoholics. There has been significant correlation between the SOCRATES scale factors. This research points to the need of using motivating techniques to reduce the ambivalence, in order to increase the adhesion and to prevent relapse.